2011
DOI: 10.1371/journal.pone.0020278
|View full text |Cite|
|
Sign up to set email alerts
|

Potential Use of a Serpin from Arabidopsis for Pest Control

Abstract: Although genetically modified (GM) plants expressing toxins from Bacillus thuringiensis (Bt) protect agricultural crops against lepidopteran and coleopteran pests, field-evolved resistance to Bt toxins has been reported for populations of several lepidopteran species. Moreover, some important agricultural pests, like phloem-feeding insects, are not susceptible to Bt crops. Complementary pest control strategies are therefore necessary to assure that the benefits provided by those insect-resistant transgenic pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…AtSerpin1 was also shown to inhibit the activity of Arabidopsis AtMC9, a type‐2 metacaspase of unknown function (Vercammen et al ., ). However, other roles for AtSerpin1 have been suggested that are related to its ability to directly inhibit the proteases of herbivorous insects (Roberts and Hejgaard, ; Alvarez‐Alfageme et al ., ). Thus, the biological significance of protease inhibition by plant serpins remains to be established.…”
Section: Introductionmentioning
confidence: 97%
“…AtSerpin1 was also shown to inhibit the activity of Arabidopsis AtMC9, a type‐2 metacaspase of unknown function (Vercammen et al ., ). However, other roles for AtSerpin1 have been suggested that are related to its ability to directly inhibit the proteases of herbivorous insects (Roberts and Hejgaard, ; Alvarez‐Alfageme et al ., ). Thus, the biological significance of protease inhibition by plant serpins remains to be established.…”
Section: Introductionmentioning
confidence: 97%
“…The biological role(s) of serpins remains somewhat unclear, although there are hints in two directions. First, artificial diets containing serpins impair growth and fertility of insect pests, indicating a potential role in defence and highlighting the potential serpins hold for crop improvement (Thomas et al, 1994(Thomas et al, , 1995Yoo et al, 2000;Alvarez-Alfageme et al, 2011). Second, two putative plant target proteases of A. thaliana serpin 1 (AtSerpin1) are involved in programmed cell death (PCD), suggesting that AtSerpin1 could have a prosurvival function.…”
Section: Promiscuous Inhibitory Folds: the Mouse Trap Typementioning
confidence: 99%
“…Hence, if GM strategies are to be used, these insect pests require other GM resistance strategies. GM approaches using plant-derived lectins, agglutinin, and protease inhibitors have been shown to provide high levels of resistance to aphids and other phloem-feeding insect species (Fitches et al, 2008; Alvarez-Alfageme et al, 2011; Carrillo et al, 2011). In addition, in planta expression of RNAi-vectors that target physiologically important insect transcripts for degradation, have been shown to result in crop protection against a number of insect pests, including phloem-feeding aphids (Price and Gatehouse, 2008; Upadhyay et al, 2011; Zha et al, 2011).…”
Section: Insect Resistance In Modern-day Breedingmentioning
confidence: 99%